PENGGUNAAN EXTREME PROGRAMMING UNTUK RANCANG BANGUN APLIKASI SEKRETARIAT PAROKI (STUDI KASUS PADA GEREJA KATOLIK SANTO PETRUS PALEMBANG) - Stefanus Setyo Wibagso (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
As part of the Catholic Church organization, the Parish Secretariat has an important role in recording information relating to parishioners. The work of the Parish Secretariat staff is very helpful in supporting the Parish Priest's task in managing the administration of the Church. In its implementation in the Parish Catholic Church of St. Peter Palembang, the secretariat staff faced several problems because the application was only able to process one activity, namely documenting Baptist data. While other data processing is still done manually. The purpose of this study is to build applications that complement the shortcomings of existing applications. To produce applications that can run well and in accordance with needs, the method in the design process is needed. Extreme Programming method is the choice in this design because it is suitable for use in designing small scale applications.